Intramuscular Clodronate in Long-Term Treatment of Symptomatic Knee Osteoarthritis: A Randomized Controlled Study - Bruno Frediani (Drugs in R&D, 2020)
Abstract Background and Objective Clodronate is a nitrogen-free bisphosphonate that is widely and effectively used in the treatment of many osteo-metabolic disorders. The objective of our study was to evaluate the effectiveness of clodronate in reducing pain and bone marrow edema in knee osteoarthritis. Methods In total, 74 patients were included in the study. Group 1 received intramuscular clodronate 200 mg daily for 15 days and then once weekly for the next 11.5 months; group 2 received intramuscular clodronate 200 mg daily for 15 days and then once weekly for the next 2.5 months. Visual analog scale (VAS) scores were recorded at baseline (T0) and after 30 days (T1), 3 months (T2), 6 months (T3), 9 months (T4), and 12 months (end of study; T5). We also evaluated functional status and use of paracetamol (T0, T1, T2, T3, T4, and T5) and changes in Whole Organ Magnetic Resonance Imaging Score (WORMS; T0, T2, and T5). Results Both groups had a statistically significant reduction in VAS score until 3 months. Group 1 then experienced further VAS reductions, whereas VAS scores for group 2 progressively increased. Pain, stiffness, and physical function also showed the same trend, as did bone marrow edema extension, which was evaluated with WORMS. Conclusion Our study indicates that intramuscular administration of a therapeutic dose of clodronate followed by a maintenance dose is effective in the management of symptomatic knee osteoarthritis, improving functional outcomes and reducing pain and bone marrow edema. Prolonged treatment increases the long-term efficacy of clodronate compared with the shorter schedule.